Strengthening Agricultural Research Capacity for Viable Extension Policies in Nigeria: An Exploration of Ricoeur’s Hermeneutic Theory for Analysing Extension Research - F O Ismail; Y I Ismaila; Z Chado; J Mosugu (Journal of Agricultural Extension, 2014)
Progressively more, researchers use hermeneutic philosophy to inform the conduct of interpretive research. Analogy between the philosophical foundations of a study, and the methodological processes through which study findings are actualized, informs hermeneutic researchers to use (or develop) hermeneutic approaches to research approach through which researchers using hermeneutics can achieve congruence between philosophy, methodology and method. Ricoeur’s theory of interpretation acknowledges the interrelationship between epistemology (interpretation) and ontology (interpreter). Also, Ricoeur notes the way interpretation moves forward from raw understanding, where the interpreter has a superficial grasp of the whole of the text, to deeper understanding, where the interpreter understands the parts of the text in relation to the whole and the whole of the text in relation to its parts (the hermeneutic circle). In this way, Ricoeur’s theory of interpretation provides researchers with a method of developing inter-subjective knowledge which could aid policy advocacy, design and implementation for the professionalization of extension in Nigeria. Through exposition of the concepts of Ricoeur’s theory, which include distanciation, appropriation, explanation and understanding, guess, and validation, a hermeneutic approach to textual analysis is presented, discussed and critiqued as a way of strengthening Nigeria’s extension research capacity and relevance. Examples from Tundun-Iya Adopted Village research on farmers’ adoption of GPS for farm measurement are used to demonstrate points under discussion. It is suggested that, in conjunction with Gadamer’s hermeneutic of understanding, Ricoeur’s theory of interpretation warrants consideration as a method of textual analysis by extension experts in Nigeria.